1994
DOI: 10.1001/archpsyc.1994.03950120017004
|View full text |Cite
|
Sign up to set email alerts
|

Backward Masking in Schizophrenia and Mania

Abstract: Schizophrenic deficits within masking paradigms may involve abnormalities in transient, as opposed to sustained, visual channels. Masking performance deficits were also found in manic patients, but the underlying processes are probably different. A reformulation is offered concerning the nature of early visual processing deficits in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(115 citation statements)
references
References 21 publications
12
102
1
Order By: Relevance
“…Previously, it has been shown that performance in .VM tasks was diminished across the schizophrenia spectrum (Green et al . 1994 a , b , 1997, 1999; Rassovsky et al . 2004; Lee et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been shown that performance in .VM tasks was diminished across the schizophrenia spectrum (Green et al . 1994 a , b , 1997, 1999; Rassovsky et al . 2004; Lee et al .…”
Section: Discussionmentioning
confidence: 99%
“…1992) The masking paradigms can require participants to locate (dorsal stream) versus identify (ventral stream) target stimuli, activating the cortical component (Balogh & Merritt, 1987; Green et al . 1994 b ; Cadenhead et al .…”
Section: Introductionmentioning
confidence: 99%
“…At the time that visual processing deficits in schizophrenia were first described, visual systems were divided into discrete “transient” and “sustained” channels based upon psychophysiological studies in humans. The backward masking deficits were interpreted as showing hyperactive transient system response (Green et al 1994), although underlying neural mechanisms were not identified.…”
Section: Bottom-up Contributions To Impaired Processing In Schizophreniamentioning
confidence: 99%
“…Green et al [103] showed impaired VBM performance in unaffected siblings of schizophrenia patients, and a few years later, the same author [104] replicated these findings in an independent sample of siblings of schizophrenia patients, but the same results were not observed in siblings of patients with different mental diseases such as bipolar disease [102]. Relatives of schizophrenia patients showed more pronounced deficits if the interval between target and mask was short and if the target location was perceived [101, 102].…”
Section: Visual Perception and Endophenotypesmentioning
confidence: 99%